Social Inequalities and Mortality in Europe - Results from a Large Multi-National Cohort - Gallo,V; Mackenbach,JP; Ezzati,M; Menvielle,G; Kunst,AE; Rohrmann,S; Kaaks,R; Teucher,B; Boeing,H; Bergmann,MM; Tjonneland,A; Dalton,SO; et al. (PLOS One, 2012)
Background: Socio-economic inequalities in mortality are observed at the country level in both North America and Europe.The purpose of this work is to investigate the contribution of specific risk factors to social inequalities in cause-specificmortality using a large multi-country cohort of Europeans.Methods: A total of 3,456,689 person/years follow-up of the European Prospective Investigation into Cancer and Nutrition(EPIC) was analysed. Educational level of subjects coming from 9 European countries was recorded as proxy for socioeconomicstatus (SES). Cox proportional hazard model’s with a step-wise inclusion of explanatory variables were used toexplore the association between SES and mortality; a Relative Index of Inequality (RII) was calculated as measure of relativeinequality.Results: Total mortality among men with the highest education level is reduced by 43% compared to men with the lowest(HR 0.57, 95% C.I. 0.52–0.61); among women by 29% (HR 0.71, 95% C.I. 0.64–0.78). The risk reduction was attenuated by 7%in men and 3% in women by the introduction of smoking and to a lesser extent (2% in men and 3% in women) byintroducing body mass index and additional explanatory variables (alcohol consumption, leisure physical activity, fruit andvegetable intake) (3% in men and 5% in women). Social inequalities were highly statistically significant for all causes ofdeath examined in men. In women, social inequalities were less strong, but statistically significant for all causes of deathexcept for cancer-related mortality and injuries.Discussion: In this European study, substantial social inequalities in mortality among European men and women whichcannot be fully explained away by accounting for known common risk factors for chronic diseases are reported.